Tree diversity is not always a strong driver of soil microbial diversity: a 7‐yr‐old diversity experiment with trees. Issue 4 (2nd April 2019) - Rivest, Maxime; Whalen, Joann K.; Rivest, David
Abstract: Trees provide organic substrates in the form of root exudates, litterfall, and fine root turnover. They modify soil physical properties and support soil biological activities. Therefore, trees are hypothesized to control soil biodiversity in forested areas. We predicted that (1) experimental forest plantations with higher tree alpha‐diversity have greater soil microbial alpha‐diversity and (2) that plantations with more divergent tree community composition would have more divergent soil microbial assemblages (Whitaker's beta‐diversity). We tested these predictions by measuring soil bacteria and fungi in a 7‐yr‐old tree biodiversity experiment. The experimental plantation contained 37 different tree assemblages, which were composed of one to four native species from temperate mixed deciduous forests. Further, there was a gradient of functional diversity nested within each level of species diversity. Soil samples were assessed for bacteria and fungi by amplicon sequencing. Tree alpha‐diversity weakly, but significantly, affected bacterial alpha‐diversity, without affecting fungal alpha‐diversity. Tree community composition was weakly, but significantly, linked to soil bacterial and fungal assemblages. In these 7‐yr‐old experimental plantations, tree diversity was not the most influential driver of soil microbial diversity.